Database of metal(loid)s and physicochemical parameters in Swedish stormwater and snowmelt runoff - Beryani, Ali; Lindfors, Sarah; Müller, Alexandra; Blecken, Godecke-Tobias; Lundy, Lian; Österlund, Helene; Viklander, Maria (Luleå University of Technology, 2026)
The database comprises 15 datasets collected at 15 stormwater and snowmelt runoff monitoring sites across Sweden, covering 182 events from 2000 to 2023, including 117 stormwater and 65 snowmelt events, as well as 40 dry-weather sewer baseflow samples. The database comprises event mean concentration of 20 metal(loid)s (total, dissolved, and bioavailable), key physicochemical parameters including total suspended solids (TSS), total and dissolved organic carbon (TOC and DOC), turbidity (Turb), pH, electrical conductivity (EC) and temperature, as well as rainfall characteristics and runoff flow data.

Databasen omfattar 15 dataset insamlade vid 15 övervakningsplatser för dagvattenavrinning och snösmältningsavrinning i Sverige, och täcker 182 händelser från 2000 till 2023, inklusive 117 dagvattenhändelser och 65 snösmältningshändelser, samt 40 torrvädersprover av basflöde i avloppssystem. Databasen innehåller händelsemedelkoncentrationer av 20 metaller och metalloider (totala, lösta och biotillgängliga), centrala fysikalisk-kemiska parametrar inklusive totalt suspenderat material, totalt och löst organiskt kol, turbiditet, pH, elektrisk konduktivitet och temperatur, samt nederbördsegenskaper och avrinningsflödesdata.
Databas över metall(loider) och fysikalisk-kemiska parametrar i svenskt dagvatten och snösmältningsavrinning
Keywords: stormwater systems; dagvattensystem; ~ metal compounds; metals; water runoff; metals; metaller; snösmältning; snowmelt; Engineering and Technology; Teknik; Water Engineering; Vattenteknik; Environmental Engineering; Naturresursteknik; Other Environmental Engineering; Annan naturresursteknik; Water Treatment; Vattenbehandlingsbioteknik